Wpływ zmian strukturalnych na tempo wzrostu gospodarczego - Onufer, Aneta (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
Many economic theories describe the relationship between the structural change and the economic growth. According to the majority of them, there is a clear indication that the economic growth is driven by the structural change. This article serves as an analysis of the connections between the structural changes and the changes in the rate of economic growth. The economic crisis which started in the United States at the end of 2007 is recognized as one of the longest, if not the longest, recession that has occurred since World War II. Having the discussion about the causes of this crisis, it seems important to ask whether there are links between the structural changes and the slowdown of the economy. It is usually assumed that the economy development is connected with the changes in the structure of production. One opposing view to this point is the Kossow–Moore hypothesis, which underlines the negative relation between the economic growth and the high structural change index. Having presented the examples of the American and French economies, the article tries to verify whether the structural change in the USA in 2006 could have infl uenced the economic crisis which started one year later.
Keywords: zmiany strukturalne; wzrost gospodarczy